Riglyne vir die ontwikkeling van 'n professionele ontwikkelingsprogram ooreenkomstig 'n werkswinkel-, ondersteunings- en mentorskapmodel (WOM-model) - Marais, Elma; Nel, Carisma; Du Toit, Christine (Suid-Afrikaanse Akademie vir Wetenskap en Kuns, 2015)
The South African education system is in a process of change yet again. An important aspect of change in the education system is the professional development of in-service teachers. According to the South African Department of Basic Education the implementation of a professional development programme can be very valuable because it transforms and enriches the education system. According to the Department of Basic Education, teachers and principals need to understand the importance of a professional development programme because this will add value to the development of teachers. When a professional development programme is developed, it is important that great caution is taken especially with the main aspects of a professional development programme. These aspects firstly include who should be presenting the professional development programme and who should attend the programme. Secondly, what (type of content) should be included in the specific professional development programme and thirdly, how (format of) the professional development programme should be presented to the attendees. Besides the above mentioned aspects that have to be considered some organisational features also have to be taken into account when planning and presenting a professional development programme. When planning a professional development programme the Department of Basic Education policy, namely the Curriculum Assessment Policy Statement (CAPS) has to be taken into account. The school, Department of Basic Education and higher education institutions have to be part of the process in order to make the programme as effective and sustainable as possible. Furthermore, the access and scope have to be taken into account, namely when and where the programme will be presented, and what it will cost will have to be explored. The programme should also be evaluated by interested parties and experts in the field. The last feature that has to be considered is the resources that are required. The tools and resources for the presentations and the tools and resources that will be presented to attendees in order to make the programme as effective as possible, need to be considered. According to Spera et al. (2009:1150), learners' academic achievement is influenced by the knowledge of teachers, the curriculum and the management of the school, and this is the main reason why professional development is important. Teachers' continuing professional development has to be encouraged to give teachers the support in the changing environment of schooling. When teachers attend a professional development programme they usually get the opportunity to adjust to the changing elements of education. These elements include the content, pedagogical knowledge, demographic changes, innovation in the school environment and social and cultural changes. Professional development programmes have to be active, constructive and problem orientated. For this reason, a W (workshop), S (support) and M (mentorship) programme is suggested. This professional development programme structure is used in order to give teachers the relevant information and to support teachers in their workplace with components they may not yet have mastered. The mentorship component of the programme gives teachers a forum to ask questions about, for example, the components of the curriculum they might find challenging. This article focuses on the presentation of practical guidelines for the planning and presentation of a professional development programme.
Guidelines for the development of a professional development programme in accordance with a workshop, support and mentorship model (WSM-model)
Keywords: Professional development; professional development programme; planning; professional development model; workshop; support; mentorship; policy; infrastructure; professionele ontwikkeling; professionele ontwikkelingsprogram; beplanning; model; werkswinkel; ondersteuning; mentorskap; beleid; infrastruktuur